Infracriticism and Interartistic Dialogue: Book review: Laura Pavel, “Personaje Ale Teoriei, Ființe Ale Ficțiunii. Eseuri / Characters of Theory, Beings of Fiction. Essays.” (Iași: Institutul European, 2021) - SELEUȘAN, Cristina (Studia Universitatis Babeș-Bolyai Dramatica, 2021)
The interpretive approach that Laura Pavel[1] engages with in her recent book Personaje ale teoriei, fiinţe ale ficţiunii. Eseuri/ Characters of Theory, Beings of Fiction, Essays[2] is a novelty in the realm of Romanian critical discourse, due to both the manner of arguing via the “characters” / beings of fiction, and the way of exposing the framework of postcritical theory. The latter supplements the current directions of interpretation in the field of literary studies, or in those of the visual and performing arts. [1]. Laura Pavel is an essayist and literary and theatrical critic, professor at the Faculty of Theatre and Film of Babeş-Bolyai University, where she teaches Theatre History, Theatre Anthropology, Cultural Studies and Performance Theory. [2]. Laura Pavel, Personaje Ale Teoriei, Ființe Ale Ficțiunii. Eseuri (Iași: Institutul European, 2021).